Cooperation, ecology and behaviour in the honeyguide-human mutualism - Lloyd-Jones, David John (Department of Biological Sciences, 2025)
This thesis explores several behavioural and ecological aspects of the human-honeyguide mutualism, a unique interspecies interaction in which greater honeyguides (Indicator indicator) cooperate with humans by guiding them to wild bees' nests. This mutualism enables each species to obtain a high-calorie, preferred food: wax for honeyguides and honey for humans. This foraging cooperation is an intriguing example of a vertebrate-vertebrate mutualism in which humans are half of the partnership, making it particularly tractable for study. Working with a community of honey-hunters in Niassa Special Reserve, northern Mozambique, I investigated: (1) the costs and benefits of the mutualism to both species, in relation to variation in cooperative interactions over time and space, (2) the exploitation of wax rewards by honeyguides and other wax-eating species, (3) whether and why honeyguides sometimes guide humans to animals other than bees, and (4) the impact and sustainability of honey-hunting on miombo tree ecology, and how this is influenced by honeyguides. I found, first, that human-honeyguide cooperation resulted in an increased rate of finding bees' nests for humans, from which both partners overwhelmingly gained a benefit. Interaction rates at the study site occurred over a large area and remained stable from 2017–2022 which, together with the apparently low costs of failed interactions, maintains the mutualism. Second, I found that the exploitation of wax rewards by conspecifics and other wax-eating animals did not jeopardize the mutualism, highlighting how wider ecological influences contribute to mutualistic persistence. Five mammalian and bird species recorded as wax-competitors were not previously known to consume wax. Third, I found evidence that honeyguides rarely but deliberately guide humans to animals other than bees, yet this behaviour (often culturally attributed to punishment) was not linked to prior rewarding or non-rewarding behaviour by honey-hunters. This and observational evidence best support the hypothesis that guiding to non-bee animals results from a cognitive recall error of spatial information. Lastly, I found that although honey-hunters frequently fell trees to harvest honey, at the landscape level the influence of honey-hunters on tree populations was spread over many tree species and sizes, at low densities, and that human-honeyguide cooperation likely further reduces this impact by leading honey-hunters to smaller-sized trees. This work draws together findings from several disciplines, linked by the central human-honeyguide relationship, to provide insights into how a mutualism both shapes and is shaped by ecological, behavioral, and cultural factors, and contributes to our understanding of mutualistic interactions.